Diabetic Ketoacidosis (DKA) at Diabetes Diagnosis in Children (0-18 years) in Ontario, Canada: A Population-Based Retrospective Cohort Study of Health Administrative Data - Oxana Mian; Elizabeth Wenghofer; Nancy Young; Liisa Jaakkimainen (International Journal of Population Data Science, 2018)
Introduction Diabetic ketoacidosis (DKA), a life-threatening complication of diabetes, is the leading cause of mortality and disability in children. The high cost of care for DKA and negative consequences of DKA on child’s health are known; however, the pediatric DKA trends in Ontario were not studied in the last fifteen years.